Implementation of Production and Cost Accounting Systems to Strengthen MSME Competitiveness: Seblak Prasmanan Ceu Nia - Yustin Nur Faizah; Nur Ajizah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to evaluate the implementation of Production and Cost Accounting Information Systems (AIS) in improving operational efficiency and competitiveness of MSMEs, with a case study on Seblak Prasmanan Ceu Nia in West Kotawaringin, Central Kalimantan. Using a descriptive qualitative approach with an exploratory case study design, this research involved two purposively selected key informants, namely the business owner and the financial staff. Data were collected through participatory observation and semi-structured interviews, then analyzed using the Miles and Huberman interactive model which includes data reduction, data display, and conclusion drawing. The results showed that the simple Excel-based system and manual notes were able to improve the consistency of recording, clarify the calculation of Cost of Goods Manufactured (COGS), and assist decision-making based on actual data. In addition, the system also strengthens the professional image of the business, increases customer trust, and opens access to financing. This research makes an important contribution to the development of accounting information systems that are contextual, flexible, and can be implemented by MSMEs with digital limitations.